Visualization Recording and Storage of Pressure Distribution through a Smart Matrix Based on the Piezotronic Effect. Issue 26 (3rd May 2017) - Han, Xun; Du, Weiming; Chen, Mengxiao; Wang, Xiandi; Zhang, Xiaojia; Li, Xiaoyi; Li, Jing; Peng, Zhengchun; Pan, Caofeng; Wang, Zhong Lin
Abstract : Pressure sensors that can both directly visualize and record applied pressure/stress are essential for e‐skin and medical/health monitoring. Here, using a WO3 ‐film electrochromic device (ECD) array (10 × 10 pixels) and a ZnO‐nanowire‐matrix pressure sensor (ZPS), a pressure visualization and recording (PVR) system with a spatial resolution of 500 µm is developed. The distribution of external pressures can be recorded through the piezotronic effect from the ZPS and directly expressed by color changes in the ECD. Applying a local pressure can generate piezoelectric polarization charges at the two ends of the ZnO nanowires, which leads to the tuning of the current to be transported through the system and thus the color of the WO3 film. The coloration and bleaching process in the ECD component show good cyclic stability, and over 85% of the color contrast is maintained after 300 cycles. In this PVR system, the applied pressure can be recorded without the assistance of a computer because of the color memory effect of the WO3 material. Such systems are promising for applications in human‐electronic interfaces, military applications, and smart robots. Abstract : A pressure visualization and recording system is achieved by integrating a piezotronic pressure sensor and a WO3 electrochromic device (ECD). In this system, the pressure is expressed by color changes in the ECD, and the color change can be retained. Such systems may have applications in human–electronic interfaces, military applications, and smart robots.